(-7+4x)(1+3x)=0

Simple and best practice solution for (-7+4x)(1+3x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-7+4x)(1+3x)=0 equation:


Simplifying
(-7 + 4x)(1 + 3x) = 0

Multiply (-7 + 4x) * (1 + 3x)
(-7(1 + 3x) + 4x * (1 + 3x)) = 0
((1 * -7 + 3x * -7) + 4x * (1 + 3x)) = 0
((-7 + -21x) + 4x * (1 + 3x)) = 0
(-7 + -21x + (1 * 4x + 3x * 4x)) = 0
(-7 + -21x + (4x + 12x2)) = 0

Combine like terms: -21x + 4x = -17x
(-7 + -17x + 12x2) = 0

Solving
-7 + -17x + 12x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-1 + -3x)(7 + -4x) = 0

Subproblem 1

Set the factor '(-1 + -3x)' equal to zero and attempt to solve: Simplifying -1 + -3x = 0 Solving -1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -3x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -3x = 0 + 1 -3x = 0 + 1 Combine like terms: 0 + 1 = 1 -3x = 1 Divide each side by '-3'. x = -0.3333333333 Simplifying x = -0.3333333333

Subproblem 2

Set the factor '(7 + -4x)' equal to zero and attempt to solve: Simplifying 7 + -4x = 0 Solving 7 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -4x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -4x = 0 + -7 -4x = 0 + -7 Combine like terms: 0 + -7 = -7 -4x = -7 Divide each side by '-4'. x = 1.75 Simplifying x = 1.75

Solution

x = {-0.3333333333, 1.75}

See similar equations:

| 35z+500=55z | | x-2=5x+8 | | 2.7+10m=8.58 | | -5(5-5m)= | | 6(3+5x)-5=43 | | 2(-2x+3)=20+6 | | 2970x(198x-178)-7921=0 | | -5t^2+40t+100=0 | | 2970(198x-178)-7921=0 | | -1.4(x-15)=2.4(x-0.5) | | 3p+2=-29 | | 2k^2-9k+11=4 | | 4(a-8)=-48 | | 3(y-2)+15=-5(y-7)-10 | | y^2=-4y-10 | | 5n+6-3n=3.7 | | 4x+3y+6z=2825 | | 72=6x+4(x-12) | | 4k+h=-2k-144 | | 4x-134+18=4x-32 | | x(x-6)= | | 6(6x-6)+6=8x-8 | | 3j+4=19 | | 7x+8-22=44-7x | | 2x^2+6x-5=85+x^2+1 | | 30(198x-178)-7921=0 | | Y+18=5y-10 | | 4+2r=10 | | 3(y-2)+15=-5(q-7)-10 | | 115=2x+7(4x-5) | | -8w-14=34 | | 4+2g=8 |

Equations solver categories